Embodied Contradictions and Post-Industrial Built Environments: From Miner Hospital to Museum of Labor Medicine in Real del Monte, Mexico - Bross, Benjamin A. (Enquiry The ARCC Journal for Architectural Research, 2023)
In October of 2004, the Museo de Medicina Laboral (Museum of Labor Medicine), opened to the public in Real del Monte, State of Hidalgo, Mexico. The museum, located on the grounds of what had been the Hospital Minero (Mining Hospital), was a building complex conceived, built, and operationalized at the height of Mexico’s Industrial Revolution and the region’s only medical facility specializing in the healthcare needs of miners and their families. Utilizing historical analysis, the hospital reveals contradictions frequently embodied by the era’s Modernist built environments. Inaugurated in 1907, the hospital was the culmination of the United States Smelting Refining and Mining Company (USSRMC) and its Mexican subsidiary, Compañía Real del Monte y Pachuca’s (CRMyP) efforts to bring healthcare to its employees while maximizing production. On one hand, the hospital’s design and operation expressed an optimism wrought by the dissemination of positivist and utilitarian philosophies and economic growth spurred by technological innovation; on the other, growing wealth inequality and deteriorating, often brutal, labor conditions. Nearly 120 years later, the hospital again embodies a global reality. In contemporary post-industrialist economies, once these built environments cease being productive, they are usually abandoned or demolished; only a few are transformed and repositioned for other uses. As the region’s mining industry ceased productivity, the hospital was first abandoned and later rescued by a newly privatized enterprise that donated the medical building complex to a non-for-profit civil association focused on mining heritage. Now the Museum, an architectural expression that fused global and local economic, technological, and aesthetic sensibilities, has become an example of commodified didactic heritage.